Childhood Nutrition In Karnataka. - Mutharayappa, R. (2012)
This paper examines various issues pertaining to nutrition of children in Karnataka. It focuses in particular on the factors which lead to under-nutrition, anemia, and stunted growth. The analysis is based on the data available from the National Family Health Surveys (NFHS) conducted during 1998-99 and 2005-06. The study finds that the cases of stunted growth had increased in the relevant period. Stunting was more rampant in rural areas. At the same time, some improvement was observed in the case of underweight and wasted children. Nearly one-third children were still found to be anemic, but incidence of severe and moderate anemia had decreased. Undernourishment was found to have a strong relationship with mother’s nutrition as well as her social background and educational level. Children were more severely malnourished if their mothers were illiterate; came from Muslim, scheduled castes and scheduled tribes background; or worked in agricultural sector. The data also reveals that there was widespread discrimination against girls in feeding practices.